RESTORATION OF TRADITIONS IN THE DEVELOPMENT OF PROVINCIAL SLOBOZHANSKY SACRED ARCHITECTURE - Eroshkina О.; Ivanov О.; Vintaev, D. (Municipal economy of cities. Series: «Economy science», 2023)
In this way, the two living cosmos of the spiritual and sacred - ethnos and theos - are combined again, the times of the creation of elite (aristocratic-official) architectural and artistic culture - the baroque and classicist tradition - are combined with the continuous time-space of folk sacred culture. The meaningful series of complex and largely forgotten spiritual symbols, which, however, constitute the deep essence of the folk tradition, are reunited. It has been proven. that the first nationally conscious and effective searches for a new uniqueness and originality of national architecture and art originate precisely from the era of modernism and ethnically rooted folk-style (national-romantic) architecture genetically related to this trend. It has been proven that one of the Slobojan architects who successfully developed deep traditions of temple architecture in the modern era was the last Kharkiv diocesan architect (1907-1917) Volodymyr Mykolayovych Pokrovsky. Namagannya yaknaishvidshe to remember three-quarters of the delay in an hour of miserable panuvannya of the atheistic sovereign doctrine of the treasury of sacral architecture once again forced professional designers to turn around until the nadban of the past. After a long break and severe wrongful losses, the creative artists of susilla and mystetsky distillation in the gallery mastered the new and traditional plastic richness of modern church symbols. As in the largest places and creative processes, the processes are least painless, in the regional periphery there is a pardon and a little mor. And it’s not less than the fact that the most ruins appeared here in the past, ale th, the main rank, the one who traditional innovations at the most important gallery, the sacred everyday life was long overdue, stretching out life for many generations, pcs scientifically rapist prizupineno. Tim more importantly assess the whole depth of the living tradition of Slobozhan sacred architecture can be directly far away.